Гнездовая орнитофауна сельских населенных пунктов Приднестровья - Тищенков, А.А. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
Surveys in Dniester Region's villages were carried out in 2002. 46 species of 7 orders, namely, Ciconiiformes - 1, Columbiformes - 3; Strigiformes - 2; Apodiformes - 1; Coraciiformes - 1; Piciformes - 2; Passeriformes - 36 species were registered. The total number was about 1757.1 pairs/km2. House Sparrow and Barn Swallow are the dominants. The majority of birds nesting in villages belong to the European and Transpalearctic types of the fauna, to the nemoral and desert-mountains landscape-genetics faunistics complexes, to the dendrophilous and sclerophyllaus ecological groups, to the entomophagous and phytophagous trophic groups.